Guided Relaxation-Based Virtual Reality for Acute Postoperative Pain and Anxiety in a Pediatric Population: Pilot Observational Study - Vanessa A Olbrecht; Keith T O'Conor; Sara E Williams; Chloe O Boehmer; Gilbert W Marchant; Susan M Glynn; Kristie J Geisler; Lili Ding; Gang Yang; Christopher D King (JMIR Publications, 2021)
BackgroundDistraction-based therapies, such as virtual reality (VR), have been used to reduce pain during acutely painful procedures. However, distraction alone cannot produce prolonged pain reduction to manage sustained postoperative pain. Therefore, the integration of VR with other pain-reducing therapies, like guided relaxation, may enhance its clinical impact. ObjectiveThe goal of this pilot study was to assess the impact of a single guided relaxation-based VR (VR-GR) session on postoperative pain and anxiety reduction in children. We also explored the influence of pain catastrophizing and anxiety sensitivity on this association. MethodsA total of 51 children and adolescents (7-21 years) with postoperative pain and followed by the Acute Pain Service at Cincinnati Children's Hospital were recruited over an 8-month period to undergo a single VR-GR session. Prior to VR, the patients completed 2 questionnaires: Pain Catastrophizing Scale for Children (PCS-C) and the Child Anxiety Sensitivity Index (CASI). The primary outcome was a change in pain intensity following the VR-GR session (immediately, 15 minutes, and 30 minutes). The secondary outcomes included changes in pain unpleasantness and anxiety. ResultsThe VR-GR decreased pain intensity immediately (P<.001) and at 30 minutes (P=.04) after the VR session, but not at 15 minutes (P=.16) postsession. Reductions in pain unpleasantness were observed at all time intervals (P<.001 at all intervals). Anxiety was reduced immediately (P=.02) but not at 15 minutes (P=.08) or 30 minutes (P=.30) following VR-GR. Patients with higher CASI scores reported greater reductions in pain intensity (P=.04) and unpleasantness (P=.01) following VR-GR. Pain catastrophizing was not associated with changes in pain and anxiety. ConclusionsA single, short VR-GR session showed transient reductions in pain intensity, pain unpleasantness, and anxiety in children and adolescents with acute postoperative pain. The results call for a future randomized controlled trial to assess the efficacy of VR-GR. Trial RegistrationClinicalTrials.gov NCT04556747; https://clinicaltrials.gov/ct2/show/NCT04556747